Reliability and validity of field-based fitness tests in youth soccer players - Dugdale, J. H.; Arthur, C. A.; Sanders, D.; Hunter, A. M. (European Journal of Sport Science, 2019)
This study aimed to establish between-day reliability and validity of commonly used field-based fitness tests in youth soccer players of varied age and playing standards, and to discriminate between players without ("unidentified") or with ("identified") a direct route to professional football through their existing club pathway. Three-hundred-and-seventy-three Scottish youth soccer players (U11-U17) from three different playing standards (amateur, development, performance) completed a battery of commonly used generic field-based fitness tests (grip dynamometry, standing broad jump, countermovement vertical jump, 505 (505COD) and T-Drill (T-Test) change of direction and 10/20 m sprint tests) on two separate occasions within 7-14 days. The majority of field-based fitness tests selected within this study proved to be reliable measures of physical performance (ICC = 0.83-0.97; p < .01). However, COD tests showed weaker reliability in younger participants (ICC = 0.57-0.79; p < .01). The field-based fitness testing battery significantly discriminated between the unidentified and identified players; Chi2 (7) = 101.646, p < .001, with 70.2% of players being correctly classified. We have shown field-based fitness tests to be reliable measures of physical performance in youth soccer players. However, results from the 505COD and T-Test change of direction tests may be more variable in younger players, potentially due to complex demands of these tests and the limited training age established by these players. While the testing battery selected in this study was able to discriminate between unidentified and identified players, findings were inconsistent when attempting to differentiate between individual playing standards within the "identified" player group (development vs. performance).